Prospective study evaluating the effect of mifepristone on E-cadherin expression in villi in early pregnancy. (November 2015) - Zheng, X.; Sun, Y.; Zhang, H.; Zhao, X.; Li, M.
Abstract: Background: E-cadherin plays an important regulatory role in implantation, embryo development and placentation. This study aimed to determine the effect of mifepristone on E-cadherin expression in human villi in early pregnancy. Study design: Forty healthy women seeking elective pregnancy termination at 5–7 weeks of gestation were recruited. Of these, 22 women chose medical termination (mifepristone-treated group) and took 25 mg mifepristone every 12 h for 3 days and 600 μg buccal misoprostol on the morning of the fourth day. The other 18 women underwent vacuum aspiration (control group). Following collection of villi, E-cadherin protein expression was assessed by immunohistochemical analysis, and E-cadherin mRNA expression was assessed by reverse transcription-polymerase chain reaction. Results: E-cadherin protein expression was significantly higher ( p  < 0.05) in villous cytotrophoblast cells in the mifepristone-treated group compared with the control group. E-cadherin mRNA expression was also significantly higher ( p  < 0.01) in the mifepristone-treated group compared with the control group. Conclusion: E-cadherin expression in villi may be involved in mifepristone-induced pregnancy termination.